space - Grigoryeva, Elena (project baikal, 2024)
A thing, being placed in space, like in aitch-two-oh, despising the risk, longs to displace the space; but your eye does not notice the splashes of space on the floor. J. Brodsky. Dedication to a chair ‘Space’ is one of the most popular and, at the same time, the most ambiguous words in the theory and practice of architecture. Perhaps there is not a single philosopher, urbanist or designer who would not use it in their work. The materials of the current issue of our journal include a wide range of reflections on the essence and properties of space – from criticism of established ideas in practical architecture to reflections on the metrics of structured, meaning-forming space of the modern city. Space in our consciousness is inextricably linked to the concept of North and South. The hot, arid and antiquities-rich South and the cold, seemingly unfriendly, but in its own way beautiful and promising North. We have divided these notions, although in fact there is no unambiguous border between them. It is even more difficult to define the boundary between the West and the East. Nevertheless, we include a selection of materials from our regular authors, researchers of architecture of the Far East. And the usual coordinates disappear completely when we start to fantasize about architecture in outer space. As usual, we do not pretend to exhaustively cover the immense topic of Space. Rather, our goal was to ask as many meaningful questions as possible and to bring many different opinions into contact.